ANALGESIC ACTIVITY OF ETHANOLIC EXTRACT OF PORTIERIA HORNEMANNII (LYNGBYE) P. C. SILVA IN MANDAPAM, RAMANADHAPURAM, TAMIL NADU, INDIA - ATHI LAKSHMI S; JOHN PETER PAUL J (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present study intends to detect the analgesic activity of the ethanolic extract of Portieria hornemannii collected from Mandapam, Ramanathapuram district, Tamil Nadu, India. Methods: Diclofenac sodium (100 mg/kg) was the standard. The analgesic activity of P. hornemannii was predicted on intact rats by tail flick latency in the Tail Immersion Method. The various concentrations of the ethanolic extracts were used as 200 mg/kg and 400 mg/kg, considering the body weight of mice. The control group received a typical saline solution. Results: The present study shows that the doses (200 mg/kg and 400 mg/kg body weight of mice) of the ethanolic extracts of P. hornemannii have brought out the analgesic activity. Conclusion: The conclusion of the study is that the ethanolic extracts of P. hornemannii Silva at 400 mg/kg showed more effect than the 200 mg/kg ethanolic extract.